2021
DOI: 10.1002/dmrr.3490
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐chain amino acids at supraphysiological but not physiological levels reduce myotube insulin sensitivity

Abstract: Aims Branched‐chain amino acids (BCAA) are often emphasized in the diets of avid exercisers, yet population data demonstrates a correlation between circulating BCAA and insulin resistance. However, it is unclear if BCAA independently promote insulin resistance in otherwise healthy cells. The purpose of this study is to examine the effect of a BCAA mixture on muscle insulin signaling in vitro in both insulin resistant and sensitive cells. Materials and Methods C2C12 myotubes were treated with a BCAA mixture con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(136 reference statements)
2
3
0
Order By: Relevance
“…Senesi et al demonstrated treatment with myotubes with 5‐Aza for 24 h was sufficient to reduce total DNA methylations measured via elisa 29 . Insulin resistance was accomplished by the addition of insulin at 100 nM for the final 3 days of differentiation (and during the treatment period) similar to previous experiments 30–32 . Insulin resistance was confirmed during the present experiments via pAkt expression following insulin stimulation (Figure S1).…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…Senesi et al demonstrated treatment with myotubes with 5‐Aza for 24 h was sufficient to reduce total DNA methylations measured via elisa 29 . Insulin resistance was accomplished by the addition of insulin at 100 nM for the final 3 days of differentiation (and during the treatment period) similar to previous experiments 30–32 . Insulin resistance was confirmed during the present experiments via pAkt expression following insulin stimulation (Figure S1).…”
Section: Methodssupporting
confidence: 84%
“…29 Insulin resistance was accomplished by the addition of insulin at 100 nM for the final 3 days of differentiation (and during the treatment period) similar to previous experiments. [30][31][32] Insulin resistance was confirmed during the present experiments via pAkt expression following insulin stimulation (Figure S1). DNA methylation was assessed using dot blot which revealed reduced DNA methylation in 5-Aza-treated cells (Figure S2).…”
Section: Cell Culturesupporting
confidence: 72%
See 1 more Smart Citation
“…BCAA-induced activation of the mTOR/p70S6K pathway has been shown by multiple rodent studies [ 3 , 133 , 146 , 181 , 182 , 185 , 186 ] and cell culture experiments [ 187 189 ]. In addition, in vivo and in vitro BCAA deprivation in mice reduced the activation of the mTOR pathway and increased pAkt in liver and muscle, resulting in improved insulin sensitivity [ 190 192 ]. Interestingly, Newgard et al reported that dietary BCAA-induced mTOR activation only occurred in the presence of a high fat load [ 3 , 104 ].…”
Section: How Do Plamsa Bcaa Levels Link To Insulin Resistance?mentioning
confidence: 99%
“…BCAA-induced activation of the mTOR/p70S6K pathway has been shown by multiple rodent studies (3,133,146,181,182,185,186) and cell culture experiments (187)(188)(189). In addition, in vivo and in vitro BCAA deprivation in mice reduced the activation of the mTOR pathway and increased pAkt in liver and muscle, resulting in improved insulin sensitivity (190)(191)(192). Interestingly, Newgard et al reported that dietary BCAA-induced mTOR activation only occurred in the presence of a high fat load (3,104).…”
Section: Elevated Bcaa Levels Hamper Insulin Signaling Pathwaysmentioning
confidence: 91%